2018
DOI: 10.1152/ajpheart.00493.2018
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical arteriole constriction compromises cytosolic and mitochondrial oxygen delivery in the isolated saline-perfused heart

Abstract: The isolated saline-perfused heart is used extensively to study cardiac physiology. Previous isolated heart studies have demonstrated lower tissue oxygenation compared with in vivo hearts based on myoglobin oxygenation and the mitochondrial redox state. These data, consistent with small anoxic regions, suggest that the homeostatic balance between work and oxygen delivery is impaired. We hypothesized that these anoxic regions are caused by inadequate local perfusion due to a paradoxical arteriole constriction g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 81 publications
(136 reference statements)
1
14
0
Order By: Relevance
“…These data support the well-established notion that myoglobin has a much lower affinity for oxygen than COX, even in the intact heart, as myoglobin oxygenation occurred well before changes in mitochondria redox state ( Figure 5). This high level of deoxygenated myoglobin under control conditions is consistent with prior studies suggesting that the isolated saline perfused heart may be partially hypoxic even under control conditions 9,19,20,21,27,36 , underscoring the importance of monitoring cardiac tissue oxygenation when using this important model in cardiac physiology.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…These data support the well-established notion that myoglobin has a much lower affinity for oxygen than COX, even in the intact heart, as myoglobin oxygenation occurred well before changes in mitochondria redox state ( Figure 5). This high level of deoxygenated myoglobin under control conditions is consistent with prior studies suggesting that the isolated saline perfused heart may be partially hypoxic even under control conditions 9,19,20,21,27,36 , underscoring the importance of monitoring cardiac tissue oxygenation when using this important model in cardiac physiology.…”
supporting
confidence: 87%
“…The VWTOS data is analyzed using full spectral fitting routine based on a reference library of spectra of cardiac chromophores and the spectrum of the light source as previously described 20,22,27,35 with a simple linear least squares approach. This spectral fitting procedure compensated for overlapping absorbance spectrum and does not rely on "isobestic" wavelengths.…”
Section: +mentioning
confidence: 99%
“…There are also a few methods that are less commonly applied by which oxygen tension can be estimated indirectly. The Balaban laboratory, for example, developed a system to assess the redox status of endogenous mitochondrial chromophores in the isolated perfused heart [ 59 ]. By using colour deconvolution, it is possible to measure the redox status of cytochrome c oxidase in the electron transport chain, which, due to its function of reducing oxygen to form water, therefore corresponds with mitochondrial oxygen tension.…”
Section: Metabolic Statusmentioning
confidence: 99%
“…As described, the fiber optic provides the ability to alternate white light with the laser, allowing us to measure changes in the cytochromes and cytoplasmic myoglobin with the alternating white light illumination. We analyzed the spectra data as described previously (Bauer et al, 2019;Femnou et al, 2017;Giles et al, 2018). As shown in Figure 4A, cytochromes bH, bL, and c1 are all components of complex III, cytochrome a605 is a component of complex IV, and cytochrome c is a mobile carrier of electrons between complex III and IV.…”
Section: Analysis Of Chromophoresmentioning
confidence: 99%
“…Coupling this method with extrinsic fluorescent probes of the ionic milieu, or other properties of the cell, expands the information content of this system. With regard to the heart and heart mitochondria, recent transmission optical spectroscopy visible light studies (Chess et al, 2013;Femnou et al, 2017;Giles et al, 2018;Kuzmiak-Glancy et al, 2018) have demonstrated the detection of numerous aspects of oxidative phosphorylation, in addition to the monitoring of cytosolic oxygen via myoglobin.…”
Section: Introductionmentioning
confidence: 99%